Land use planning strategies for food versus non-food estate sustainable farming - D. Juhandi; D.H. Darwanto; M. Masyhuri; J.H. Mulyo; N.A. Sasongko; H.L. Susilawati; A. Meilin; T. Martini (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Food estate initiative is an Indonesian government program designed to achieve food security though the cultivation of strategic commodities on large-scale agricultural land. Despite being controversial due to the scale of land use and budgetary requirements, the viability of the program has been questioned by critics pointing to the failure of a similar initiative in the past. In other words, there is widespread pessimism regarding sustainability of food estate  program. Therefore, this study presents a new approach to farming sustainability investigation, assessing seven aspects including economy, society, environment, institutions, technology, market, and culture. The objective was to compare the value and status of sustainability as well as design land use planning strategies.METHODS: Respondents of the questionnaire were 50 food estate  farmers, selected from Pollung sub-district, as well as 50 non-food estate  farmers from Dolok Sanggul and Lintong Nihuta Sub-districts. Multiaspect Sustainability Analysis software was used to conduct data analysis with Multidimensional Scaling approach. Primary data was collected through interviews using questionnaires and seven aspects analyzed include economic, social, environmental, institutional, technological, marketing, and cultural, with several factors. In addition, a total of 45 indicators were used to compare sustainability of farms, including 7 economics, 6 social, 9 environmental, 5 institutional, 7 technological, 5 marketing, and 6 cultural.FINDINGS: The results showed that in Food Eestate farming, sustainability value for economic aspects was 47.57, social 50, environmental 72.22, institutional 50, technological 50, market 53.4, and cultural 33.33. On the other hand, sustainability value of non-Food Eestate farming estate was 33.29 for economic, 47.17 for social, 77.78 for environmental, 56.6 for institutional, 42.86 for technological, 36.6 for market, and 41.67 for cultural aspects. The overall sustainability value of Food Eestate farming was 50.93, which was slightly higher than non-food estate  score of 48. Improving all aspects in the third scenario is the most favorable approach for improving farming sustainability. Based on the results, 12 sustainability indicators were found to be relevant for designing land use planning strategies. These indicators had different implications for stakeholders in improving sustainability.CONCLUSION: Sustainability value of food estate  farming exceeded that of non-Food Eestate but both were in the moderate category. Higher sustainability scores were recorded in economic, social, technological, and marketing aspects for Food Eestate farming, while higher scores were found in environmental, organizational, and cultural aspects for non-food estate . This study recommended implementing land use strategies such as multiple cropping for Food Eestate farming, and crop rotation for non-food estate. To implement the strategy for Food Eesrare farming, the government needed to increase fertilizer subsidies, provide agricultural insurance, relevant technology, extension services on land leases, agricultural sustainability, and water management. For non-food estate  farming, the recommendations included providing capital loans, extension services on land tenure, agricultural sustainability, land conversion, inorganic fertilizer dosage, and weed management.